EVALUATION OF MOTIVATORS AND DEMONSTRATORS OF ACTIVITY OFENTERPRISE EMPLOYEES (Regional aspects of productive forces development of Ukraine, 2019)
The article considers motivation as a process of encouraging employees to carry out effective activities aimed at achieving the goals of the enterprise. The motivational policy of the private JSC “Roshen” is characterized to ensure personnel stability in the organization. It is considered one of the contemporary non-traditional approaches to a material incentives system through the use of compensation wage system models, designed for a long career employee. It is carried out an analysis of the demotivational factors of the corporation “Roshen” employees’ activity, which shows that in today’s working conditions personnel are in urgent need not only in motivational factors but also in hygiene ones such as working conditions, salary, interpersonal relations with a supervisor or peers, the degree of direct control over the work. The main problems of personnel motivation at private JSC “Roshen” are highlighted, and it is revealed that demotivation of employees’ activities can be considered as a significant threat to social and labour enterprise security. The measures to stimulate the employees’ activities are suggested, which will increase the satisfaction of the employees at the enterprise and significantly increase their understanding of their belonging to the entire company performance.